2007
DOI: 10.1111/j.1365-2265.2007.03121.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms associated with cigarette smoking and the risk of Graves’ disease

Abstract: We concluded that GSTP1, CYP1A1 and TP53, but not GSTT1 and GSTM1 germline polymorphisms, may be associated with smoking-related Graves' disease susceptibility and configure a risk profile for the disease. However, these polymorphisms do not influence the patients' response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Pro72TP53 homozygous inheritance was revealed as an important risk factor of GD, especially among smokers (19). Using a subset of 280 GD patients carefully paired for exposure to environmental risk factors with a control group of 284 individuals, we confirmed the data and now demonstrate that HHV-7 infection is also associated with an increased susceptibility to GD.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Pro72TP53 homozygous inheritance was revealed as an important risk factor of GD, especially among smokers (19). Using a subset of 280 GD patients carefully paired for exposure to environmental risk factors with a control group of 284 individuals, we confirmed the data and now demonstrate that HHV-7 infection is also associated with an increased susceptibility to GD.…”
Section: Discussionsupporting
confidence: 69%
“…We previously demonstrated that individuals with GSTP1 and CYP1A1 variants may be more susceptible to the effect of autoimmunity-inducing environmental or endogenous products (19). Pro72TP53 homozygous inheritance was revealed as an important risk factor of GD, especially among smokers (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Therefore, it has become generally accepted that genetic predisposition to DTC is likely due to common lowpenetrance or rare moderate-penetrance variants. 9 Moreover, there is evidence that gene-gene 10,11 and gene-environment interactions 12,13 modulate individual susceptibility. In this scenario, both carefully designed candidate-gene association studies [14][15][16] and genome-wide association studies (GWAS) [17][18][19][20] have been used to identify susceptibility variants for DTC.…”
mentioning
confidence: 99%
“…The application of this approach to late-onset POAG is the focus of current studies in this area. Bufalo et al (2008) noted that the CYP1A1m1 polymorphism is associated with increased susceptibility to Graves' disease, which can lead to manifestations such as ophthalmopathies. Regarding the distribution of the polymorphism CYP1A1m1, Santos (2009) found no statistically significant difference between the groups that developed and did not develop Graves' ophthalmopathy.…”
Section: Discussionmentioning
confidence: 99%